Pilot Development of a Critical Food Safety Message Visual Communication Tool for Farmers’ Market Vendors - Lilly W. Jan; Shannon M. Coleman; Anirudh Naig (Journal of Human Sciences and Extension, 2021)
Farmers’ markets are popular sources of fresh and ready-to-eat foods for consumers in the United States. However, research indicates that food safety practices of vendors and their employees serve as a concern for customers. This pilot study focused on assessing a visual-based, minimal-text educational tool that was disseminated to farmers’ market vendors and employees (n = 27) in Iowa. The tool was evaluated using a post-intervention survey of vendors’ and employees’ knowledge of food safety practices and their attitudes towards the educational tool. The results did not show a statistically significant increase in attitude and knowledge scores of farmers’ market vendors and employees for participants that reported seeing the food safety tool versus those that did not. However, participants did respond favorably to the food safety tool’s informative content and visual format; many indicated an interest in using the tool in their stalls in the future. The results suggest that farmers’ markets vendors and employees feel favorably towards the use of visual tools in the communication and promotion of safe food handling practices.